A study of the fresh and mechanical properties of concrete with open-heap burned rice husk ash (RHA) as a partial cement substitute and as a pozzolanic material - Jorillo, Pablo A. (1989)
This is an experimental study on the fresh and mechanical properties of concrete with rice husk as a partial cement substitute and as a pozzolanic material. The ash used in the experiments is the open-heaped up burnt and unground rice husk ash, which is very much available in the countryside. Ashes at different degrees of fineness were introduced to four kinds of grades of concrete. To determine the mechanical properties of concretes with different percentages of ash the following tests were applied: axial compression at three curing ages, split tension, third point flexure, and modulus of elasticity tests. for the fresh properties the time of setting concrete mixture, air content and plastic density were measured.
The findings revealed the feasibility of using ash from open heap burnt rice husk as a construction material, particularly for medium and low grade concrete when used as a cement substitute at a proportion of 80:20 (portland cement : ash by volume). In this proportioning, the test showed that the strength of RHA concrete is almost the same as the strength of plain portland cement concrete, and with significant reduction in costs. Thus, this viable program is most applicable in the countryside where rice husk are abundant and considered only as solid waste.
Thesis (M.S.)--University of the Philippines, Diliman.
Typescript.
Keywords: Rice hull ash; Building materials; Cement